Progress in cryptology - LATINCRYPT 2014 : third International Conference on Cryptology and Information Security in Latin America Florianópolis, Brazil, September 17-19, 2014 Revised selected papers /: third International Conference on Cryptology and Information Security in Latin America Florianópolis, Brazil, September 17-19, 2014 Revised selected papers. (2015) - Unknown
No abstract available